Designing a Model for Maturity of Commercial Soft Technology with a Cognitive Mapping Approach (Case: Poultry Cluster of Golestan Province) - Mohammad Nazari, Ali Naghi Mosleh Shirazi (Opción, 2019)
This paper aims to present a model for maturity of commercial soft technology with a cognitive mapping. The research is based on the cognitive study of poultry cluster, soft business technology model and cognitive mapping approach. The research was done using field study and documentary research methods. The results indicate that there are critical procedures at work for supplying inputs, production process and marketing technology. In conclusion, industry performers can develop competitive advantage in an unbalanced and unsustainable internal and external economy, with the development of collective participation, the formation of buying and selling networks, and by gaining skill-based knowledge.